Modic Changes in the Lumbar Spine are Common Aging-related Degenerative Findings that Parallel With Disk Degeneration. Issue 7 (August 2018) - Chen, Lunhao; Hu, Xiaojian; Zhang, Jingfeng; Battié, Michele C.; Lin, Xiangjin; Wang, Yue
Abstract : Study Design: This is a cross-sectional study. Objective: To determine the prevalence and distribution patterns of Modic changes (MCs) in the lumbar spine and their associations with disk degeneration in mainland Chinese using a sample of general population. Summary of Background Data: Previous studies reported that the prevalence of MCs in Hong Kong Chinese was much lower than in other populations. Moreover, their associations with disk degeneration need further study. Materials and Methods: The study sample consisted of 442 subjects (53.6±14.9 y; range, 20–88 y) randomly selected from a typical Chinese community. Lumbar spines were imaged using a 3.0 T magnetic resonance scanner. Eleven endplates (L1–S1) in the lumbar spine were evaluated for the presence of MCs, type, location, and size to determine MCs prevalence and distribution patterns. Disk degeneration was graded using a Pfirrmann scale. Results: MCs were present in 209 (47.3%) subjects and 593 (12.2%) endplates. Among these endplates, 84.1% (499) were type II, 9.1% (54) were type I, and 6.4% (38) were mixed MCs. Approximately 2/3 MCs were present in the lower lumbar spine and 44.9% of MCs were at the L5/S1 disk level. Most MCs (73.9%) involved both endplates of a disk. Greater age [odds ratio (OR)=2.44 for each 10-year increase, P <0.001] and body mass index (OR=1.07, P =0.016) were associated with the presence of MCs, as was adjacent disk degeneration (OR=6.00, P <0.001), controlling for age and other covariates. Greater age, body mass index, and adjacent disk degeneration were also associated with greater MCs size. Conclusions: MCs are common in mainland Chinese, with type II predominating. MCs mainly present in the lower lumbar region and tend to occur in pairs. MCs were strongly associated with age and disk degeneration, suggesting MCs may be aging-related degenerative findings that parallel disk degeneration. Level of Evidence: Level II.